A web-based survey of reproductive awareness and choices in women with endometriosis. (August 2020) - Navarria-Forney, I.; Bénard, J.; Mazloum, A.; Aerts, L.; Pluchino, N.; Streuli, I.
Abstract: Objective: Our aim was to study fertility issues, attitudes towards reproductive techniques and fertility preservation options in women of reproductive age with endometriosis. Study design: In 2018 we conducted a web-based survey on fertility issues in women aged 18–40 years with endometriosis. Participants were recruited via advertisements on social media and local endometriosis support groups. Participants completed a self-developed online questionnaire evaluating the following dimensions: sociodemographic, medical data, parental project, knowledge and attitudes toward endometriosis and fertility, means used to access information, and reproductive choices. Results: The majority of women (96 %) worried about the impact of endometriosis on their fertility. Approximately half of them (52 %) reported having received sufficient information concerning the effect of endometriosis on fertility from their doctor, whereas 31 % had discussed fertility issues with their doctor but desired further information. In contrast, only a minority (27 %) of women considered themselves well-informed on fertility preservation options. Information given by specialists on endometriosis and reproduction was considered most useful. Information mediated through patient support groups was also highly rated, whereas information given by the general gynecologist was less highly rated. The majority of women would consider assisted reproductive techniques (74 %) or adoption (70 %) in case of infertility. Interestingly, 72 % of women would undergo oocyte vitrification for fertility preservation, whereas only 37 % would resort to oocyte donation. Conclusion: This is the first survey to address the topic of fertility issues from the patient's perspective in women with endometriosis. The vast majority of women attach great importance to a discussion about fertility possibilities and only a minority of women consider themselves well-informed. Our results highlight the importance of addressing the issue of fertility in women with endometriosis. Special attention should be given to information and counselling about fertility preservation options since most women consider their knowledge on the topic insufficient. Knowledge and attitudes to counsel endometriosis patients on fertility issues and fertility preservation options should be included in the training curricula of gynecologists. Adequate information on reproductive aging, risk factors for infertility, and reproductive choices, including oocyte vitrification, should be incorporated into follow-up visits for endometriosis patients.